Desmineralização em osso trabecular e osso cortical de cães submetidos à terapia com prednisona - Costa, Lorena Adão Vescovi Séllos (2011)
Glucocorticoids are drugs widely used in veterinary medicine, however, their use can trigger a series of adverse effects. The clinical trial was aimed at evaluating possible changes in bone mineral density after therapy with prednisone, using helical computed tomography. In the study, eight healthy mongrel young adult dogs were used, 4 males and 4 females. Prednisone was administered orally to animals at a daily dose of 2mg kg-1 body weight for 30 days. Bone mineral density was determined from the radiodensity values obtained from the region of cortical and trabecular bone of the vertebral body of the second lumbar vertebra, immediately before and after the period of drug administration. The experimental protocol allowed the characterization of significant (P <0.05) decreased radiodensity of trabecular and cortical bone of vertebral body of the second lumbar vertebra, but no significant demineralization was found in the cortical region. None of the dogs of the experimental group showed pathological fracture at the end of drug administration. The study showed changes in bone metabolism in dogs subjected to therapy with prednisone at a dose of 2mg kg-1 only occur early in trabecular bone, making it a recommended monitoring patients for prevention of pathological fractures.